Clinical Manifestations and Outcomes of Colchicine Poisoning Cases; a Cross Sectional Study - Rahimi, Mitra; Alizadeh, Reza; Hassanian-Moghaddam, Hossein; Zamani, Nasim; Kargar, Alireza; Shadnia, Shahin (Archives of Academic Emergency Medicine, 2020)
Introduction: Colchicine is a medication with narrow therapeutic index, leading to both accidental and suicidal poisonings incidents. This study aimed to investigate the clinical and laboratory manifestations, as well as outcomes of colchicine poisoning patients referred to emergency department. Methods: In this retrospective cross sectional study, demographics, clinical features, laboratory parameters, and outcomes of colchicine poisoned patients who were admitted to an academic referral center, Tehran, Iran, during 7 years were extracted from the patients’ profiles and analyzed. Results: 21 patients with the mean age of 25.48 ± 12.65 years were studied (61.9% female; 85.7% suicidal). The mean ingested colchicine dose was 30.25 ± 21.09 mg. The most common symptoms were nausea and vomiting observed in 19 (90.5%) cases, followed by abdominal pain in 10 (47.6%) and diarrhea in 9 (42.8%) cases. 3 (14.3%) had died, the cause being disseminated intravascular coagulation (DIC) in two cases and severe metabolic acidosis in one. Prevalence of abdominal tenderness (p = 0.001) and abdominal pain (p = 0.049) was significantly different between survived and non-survived patients. There were significant correlations between systolic blood pressure (p = 0.010), diastolic blood pressure (p = 0.002), serum glucose (p = 0.031), calcium (p = 0.017), white blood cell (WBC) count (p = 0.043), aspartate aminotransferase (AST) (p = 0.001), alkaline phosphatase (ALP) (p = 0.012), prothrombin time (PT) (p = 0.006), partial thromboplastin time (PTT) (p = 0.014), PaCO2 (p = 0.011), DIC (p < 0.001), and need for mechanical ventilation (p = 0.024) with survival. Conclusions: Based on the findings of the present study, the mortality rate of colchicine poisoning was 14.3% and there was significant correlation between lower blood pressure, lower serum glucose and calcium levels, lower PaCO2, higher WBC count, higher AST and ALP levels, higher PT and PTT, need for mechanical ventilation, presence of DIC, and also abdominal pain and tenderness with survival.